The Influence of Attitude And Subjective Norms On Student’s (Future) Intention and Future Decision Of Higher Level Studies: A Case Study of Five Universities with BHMN Status in Indonesia - Gayatri, Gita; Alversia, Yeshika; Astuti, Rifelly Dewi (UI Scholars Hub, 2021)
Since government regulation (PP) Nu 61/1999 came into effect, competitions were heating up among state-owned universities (PTN) in attracting high school graduates. This research aims to understand students’ attitudes toward tertiary education institutions, their promotion activities and other external factors such as family, and the impact of those attitudes in choosing tertiary education institution if they were to take further study and in recommending certain tertiary education institution to other people. The sample chosen was approximately 500 first-year tertiary students from UI, ITB, IPB, UGM dan Unair.The result of this study found that students are strongly influenced by their positive attitude toward tertiary education institution, being shaped mainly by the perception on lecturers’ quality and education facility, as well as external influence that motivates them to acquire similar characteristics with that of a certain reference group exists in the respective tertiary education institution.